2015
DOI: 10.4081/ijas.2015.3713
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Live Cells or Cells Extract ofSaccharomyces Cerevisiaeonin VitroGas Production of a Total Mixed Ration

Abstract: The effect of Saccharomyces cerevisiae as live cells (LC) or cells extract (CE) on in vitro gas production (GP) kinetics and ruminal fermentation parameters of a total mixed ration (TMR) consisting of commercial concentrate and alfalfa hay [1:1 dry matter (DM)] as a substrate was studied. The TMR was incubated with CE at 1, 2 and 4 mg/g or LC at 0.3, 0.6 and 0.9 mg/g DM for 96 h. Rumen GP was recorded after 6, 12, 19, 24, 48, 72 and 96 h of incubation. Interaction effects were observed (P<0.01) between treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 36 publications
5
18
3
Order By: Relevance
“…Yeast additives had no effect on rate of GP but there was a slight increase in rate of GP compared with the control. This result is in contrast to the work of Rodriguez et al (2015) who reported a decreased rate of GP in response to SC additives. The differences in results may be due to the composition and incubation of the substrates (Elghandour et al, 2014).…”
Section: Discussioncontrasting
confidence: 99%
“…Yeast additives had no effect on rate of GP but there was a slight increase in rate of GP compared with the control. This result is in contrast to the work of Rodriguez et al (2015) who reported a decreased rate of GP in response to SC additives. The differences in results may be due to the composition and incubation of the substrates (Elghandour et al, 2014).…”
Section: Discussioncontrasting
confidence: 99%
“…Gas production is generally a good indicator of digestibility, fermentability and microbial protein production (Rodriguez et al . 2015). Higher proportions of concentrates in the rations indicate a better nutrient availability for rumen microorganisms (Elghandour et al .…”
Section: Discussionmentioning
confidence: 99%
“…Further, as described by Rodriguez et al (2015), and at the end of incubation period, bottles were uncapped and the pH was measured using a digital pH meter (Conductronic pH15.0, Puebla, Mexico), and the residual of each bottle was filtered under vacuum through glass crucibles with a sintered filter. The fermentation residues were dried at 65 C for 72 h in order to estimate DM digestibility (DMD) (Orskov and McDonald, 1979).…”
Section: In Vitro Incubationsmentioning
confidence: 99%